Overview and perspectives of solid electrolytes for sodium batteries. Issue 2 (16th November 2022) - Vasudevan, Sudharshan; Dwivedi, Sushmita; Balaya, Palani
Abstract: Quoting the abundance and cost of sodium reserve and robustly safe and high‐energy solid electrolytes, sodium solid‐state batteries (SSBs) exhibit huge promise for future energy storage applications compared to battery systems using organic liquid electrolytes and Li counterparts. However, the progress and application are still in infancy, experiencing numerous challenges for sodium SSBs due to inherent properties, interface complications, and fabrication. These are recently receiving unprecedented research attention by understanding and steadily resolving the issues associated with sodium SSBs. In this review, the governing bulk and interfacial issues and dynamics, background research correlations from Li counterparts, and strategies to address them are investigated for various ceramic‐, polymer‐, and ceramic–polymer composite based solid electrolytes. Particular attention is devoted to issues with ceramic electrolytes (such as interfacial stability, brittleness, porosity, and grain–grain boundary resistance) and polymer electrolytes (like dendrite formation, passivation layer, electrochemical instability, and ionic conductivity), and finally, robustness in overall performance and a few drawbacks (such as filler agglomeration, interface dynamics, and crack propagation) on the composited state‐of‐the‐art ceramic–polymer electrolytes are highlighted. To end with, crucial inferences and future research perspectives are condensed on the development of enhanced solid electrolytes for sodium SSBs overcoming the shortcomings illustrated for different electrolytes. Abstract :